1976
DOI: 10.1161/01.cir.53.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic determination of left atrial volumes in children with congenital heart disease.

Abstract: The feasibility of determining left atrial volumes (LAV) from LA echo dimensions was assessed in 36 children (group I) with normal cineangiographically determined LAV and 16 children (group II) with LAV overload. Conventional LA echo dimensions, obtained within 24 hours of cardiac catheterization, were compared to the angiographic LA anterior-posterior minor axes (LAmA) and LAV. There was excellent correlation betweeh the LA echo dimensions and the LAmA. In all patients, the LA echo less than LAmA, the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…In a clinical study, identical correlations were shown to exist between angiographicalry determined left atrial anteroposterior minor axes and the left atrial volume in both the normal and volume overloaded left atrium with a wide variety of lesions. 23 All these data verify the postulation that any left atrial dimension should be sufficient to evaluate the chamber size, particularly when sequential changes are to be assessed serially in a single animal. The similarity of the phasic pattern of atrial diameter to directly measured flow across the mitral valve 24 also lends support to the idea that such measurements can serve as an indicator of global performance of the left atrium.…”
supporting
confidence: 59%
“…In a clinical study, identical correlations were shown to exist between angiographicalry determined left atrial anteroposterior minor axes and the left atrial volume in both the normal and volume overloaded left atrium with a wide variety of lesions. 23 All these data verify the postulation that any left atrial dimension should be sufficient to evaluate the chamber size, particularly when sequential changes are to be assessed serially in a single animal. The similarity of the phasic pattern of atrial diameter to directly measured flow across the mitral valve 24 also lends support to the idea that such measurements can serve as an indicator of global performance of the left atrium.…”
supporting
confidence: 59%
“…Echocardiography has proved itself as a noninvasive method for determination of left atrial size with a high degree of accuracy. Measurements correlate closely with those obtained by angiography (Hirata et al, 1969;Lundstrom and Mortensson, 1974;Ten Cate et al, 1974;Yabek et al, 1976). The larger the left-to-right shunt, the greater the volume of blood delivered to the left atrium.…”
supporting
confidence: 73%
“…The left atrial dimension is affected by other factors apart from the volume of blood reaching it. Decreased left ventricular compliance will result in an increase in left atrial dimension, as will lesions of the mitral valve (Hawley et al, 1966;Yabek et al, 1976). One patient (not in this series) had a ventricular septal defect and coarctation of the aorta, and was in left ventricular failure; he had a larger left atrial dimension than expected from the size of the shunt.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Two-dimensionally guided M-mode echocardiography allows for the measurement of left atrial dimension in the parasternal long-axis orientation. M-mode-derived left atrial size has been shown to correlate well with angiographically derived left atrial areas and volumes 7 and has been used to monitor changes in left atrial size in AF. 8 -10 Left atrial enlargement is common among patients with AF.…”
Section: Role Of Transthoracic (Surface) Echocardiographymentioning
confidence: 99%